Nonlinear Parabolic-Hyperbolic Coupled Systems and Their Attractors - I. Gohberg, D. Alpay, J. Arazy, A. Atzmon, J. A. Ball, H. Bart, A. Ben-Artzi, H. Bercovici, A. Böttcher, K. Clancey, R. Curto, K. R. Davidson (Springer, 2017)
472 p.